Effect of recycling on polypropylene composites reinforced with glass fibres. (May 2017) - Colucci, Giovanna; Simon, Hadrien; Roncato, Davide; Martorana, Brunetto; Badini, Claudio
The aim of the work was to investigate the effect of recycling on the mechanical behaviour of polypropylene composites reinforced with glass fibres (GFs), starting from a material already used in automotive for vehicle components, obtained by injection moulding. Formerly specimens of pristine composites were subjected to tensile and flexural tests, then the specimens were grinded, reprocessed and recycled only once. The recycled composites showed a slight decrease in the elastic modulus and tensile and flexural strength values. Morphological investigations, carried out by scanning electron microscopy and optical microscopy, were also performed to study the microstructure and the fibre–polymer interfaces, together with the GFs' orientation and distribution within the polymeric matrix before and after the mechanical recycling. The results revealed that the mechanical recycling had no significant effect on the final microstructure and performance of the fully recycled composites, which can be still successfully used for structural applications in the automotive field.